Osteopontin neutralization increases vitamin D receptors on NKT cells and ameliorates liver fibrosis by promoting their activity - Amer, Johnny; Salhab, Ahmad; Hussini, Enas; Shweiki, Rasha; Zahran, Iman; Far, Mohammad (Frontiers in Pharmacology, 2024)
Introduction and aims: Vitamin D has an immunomodulatory property influencing the activity of NKT cells. We aimed to study the impact of osteopontin (OPN), a key driver of fibrosis, on NKT cells' vitamin D receptor (VDR) and activity alterations. Methods: Liver fibrosis was induced in BALB/C mice with carbon-tetrachloride (CCl4) for eight weeks with either vitamin D [100ng/Kg] or InVivoMAb anti-mouse OPN [100 µg/Kg] 2X/week started at week-4 of CCl4. The liver injury profile of serum ALT, AST, and inflammatory cytokines were evaluated. Histopathological findings were assessed via H&E staining and Sirius-Red staining. Fibrotic genes of αSMA, CREBP, and collagen III were assessed using RT-PCR. Fast blood sugar, insulin, liver cholesterol, and triglyceride were evaluated. Liver tissue-resident (tr)-NKT cells were obtained for VDR expressions, molecular pathways of p-STAT1 and P-STAT-5, and activation markers of CD107a and NKp46 using flow cytometry. Results: Following vitamin D treatment, H&E staining revealed reduced microvascular and macrovascular steatosis, while Sirius-Red staining showed less fibrosis accumulation in liver fibrosis mice than in untreated counterparts. Results were associated with a significant decrease in serum cytokines of IL-b/IL-6/IL-4/OPN/TNF-a and serum AST and ALT by 2-fold and 3-fold, respectively. Fibrotic markers showed an average 1.3fold decrease in αSMA, CREB, and Col-III in liver fibrosis mice following vitamin D treatment. Quantitated liver cholesterol and triglycerides, serum insulin, and fasting blood sugar ameliorated their levels following vitamin D treatment in liver fibrosis mice. OPN-neutralizing antibody overexpressed VDR on trNKT cells and increased CD107a and NKp46 activities of 3.1 and 3.5 folds, respectively, associated with increasing in p-STAT1 and p-STAT5 phosphorylation. These results were accompanied with a decrease in hepatic-stellate-cell activation markers of αSMA, Col-III, and desmin. Conclusion: VDR expressions affect trNKT cells activity and could modulate 3 progressions of liver fibrosis. Using an OPN-neutralizing antibody exhibited an antifibrotic effect by alleviating the liver injury profile through NKT cells. It is also suggested as an immunomodulatory target of liver fibrosis.